2020
DOI: 10.3390/ijms21165659
|View full text |Cite
|
Sign up to set email alerts
|

Antitumoral Drug: Loaded Hybrid Nanocapsules Based on Chitosan with Potential Effects in Breast Cancer Therapy

Abstract: Cancer remains one of the world’s most devastating diseases and is responsible for more than 20% of all deaths. It is defined as uncontrolled proliferation of cells and spreads rapidly to healthy tissue. Controlled drug delivery systems offers great opportunities for the development of new non-invasive strategies for the treatment of cancers. The main advantage of these systems is their capacity to accumulate in tumors via enhanced permeability and retention effects. In the present study, an innovative hybrid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Furthermore, Cs have the capability to form gel-nanoparticles via ionic crosslinking with polyanionic molecules, such as sodium tri-polyphosphate (TPP) [ 15 ]. Cs are also established as a nanoscopic carrier for diverse drugs, with chitosan-based nanoparticles (NPs) evolving to be one of the most accepted delivery systems for cancer chemotherapy [ 16 , 17 ]. Numerous chemical modifications, including the Schiff base formation [ 18 ], grafting [ 19 ], and quaternization [ 20 ], were conducted on native chitosan to broaden the spectrum of its biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Cs have the capability to form gel-nanoparticles via ionic crosslinking with polyanionic molecules, such as sodium tri-polyphosphate (TPP) [ 15 ]. Cs are also established as a nanoscopic carrier for diverse drugs, with chitosan-based nanoparticles (NPs) evolving to be one of the most accepted delivery systems for cancer chemotherapy [ 16 , 17 ]. Numerous chemical modifications, including the Schiff base formation [ 18 ], grafting [ 19 ], and quaternization [ 20 ], were conducted on native chitosan to broaden the spectrum of its biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the efficiency of the antitumoral treatment, hybrid nanocapsules obtained from the interfacial condensation between chitosan and poly(N-vinyl pyrrolidone-alt-itaconic anhydride), containing both magnetic nanoparticles and 5-fluorouracil, were developed. Their nanometric size and their spherical shape were confirmed by SEM [75].…”
Section: Anticancer Drugsmentioning
confidence: 84%
“…Antimicrobial and antibiotics Fluoxetine Polymeric [54] Carvacrol Polymeric [55] Amoxicillin Polymeric [56] Florfenicol Polymeric [57] Tea tree oil Polymeric [58] Fusidic acid Lipid [59] Albendazole Lipid [60] Anticancer drugs Curcumin Polymeric [61][62][63] Hybrid lipid [64] Liquid lipid [65,66] Docetaxel Polymeric [67,68] Lipid [69] Perillyl alcohol Polymeric [70] Tamoxifen Polymeric [71,72] Aprepitant Polymeric [73] 5-fluoroacil Polymeric [74,75] Doxorubicin Polymeric [76] Paclitaxel Polymeric [77,78] Lipid [79] Oleic acid Hybrid [80] Simvastatin Hybrid [81] Thymoquinone Polymeric [82] Gemcitabine Lipid [83] Phloretin Lipid [84] Itraconazole Lipid [85,86] Regorafenib Lipid [87] Sorafenib Lipid [88] Imatinib Lipid [89] Ifosfamide Lipid [90] Vinorelbine Lipid [91] Anti . Chitosan-PCL core-shell nanocapsules were obtained and loaded with tea tree oil.…”
Section: Pharmacological Group Drug/compound Type Of Nanocapsule Refe...mentioning
confidence: 99%
“…Acting as a targeted drug carrier, polymeric nanocapsules could prolong the drug’s circulation time, delay, or control the drug’s release and also improve its efficacy [ 93 ]. In a study of three different lipid nanosystems, the researchers found that, when DOX was enclosed in lipid nanocapsules, the half-maximal inhibitory concentration (IC50) decreased, implying less drug dosage and toxicity [ 94 ].…”
Section: Targeting Drug Delivery Systemsmentioning
confidence: 99%